2002
DOI: 10.1086/339822
|View full text |Cite
|
Sign up to set email alerts
|

Illness Severity, Viral Shedding, and Antibody Responses in Infants Hospitalized with Bronchiolitis Caused by Respiratory Syncytial Virus

Abstract: The relationships between host factors, viral shedding, illness severity, and antibody response in respiratory syncytial virus (RSV)-induced bronchiolitis are poorly defined. These relationships were prospectively evaluated in 77 infants hospitalized with RSV bronchiolitis in multicenter, double-blind, placebo-controlled trials of RSV immunoglobulin therapy. Severity of illness was influenced by age and host risk factors but was not influenced by RSV neutralizing antibody titer or by the amount of virus in nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
91
4
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 47 publications
16
91
4
2
Order By: Relevance
“…However, the data collected with this study are in agreement with the data published by Wright et al. 20 These authors prospectively evaluated 77 infants with RSV bronchiolitis and found that the severity of the illness was influenced by age and host risk factors but not by RSV-neutralizing antibody titres, the amount of virus nasal secretion, or the duration of viral shedding. Most children with the highest antibody response had an LRTI during the study period, suggesting a potential association between immune response and the development of disease more severe than common URTIs.…”
Section: Discussionsupporting
confidence: 91%
“…However, the data collected with this study are in agreement with the data published by Wright et al. 20 These authors prospectively evaluated 77 infants with RSV bronchiolitis and found that the severity of the illness was influenced by age and host risk factors but not by RSV-neutralizing antibody titres, the amount of virus nasal secretion, or the duration of viral shedding. Most children with the highest antibody response had an LRTI during the study period, suggesting a potential association between immune response and the development of disease more severe than common URTIs.…”
Section: Discussionsupporting
confidence: 91%
“…Infants who experience RSV infection severe enough to cause respiratory failure have~1 log PFU/mL greater nasal RSV load than those who do not (14). Although the relationship between RSV concentrations and disease severity is controversial (15,16), higher viral loads measured near the time of admission have also been shown to correlate with longer durations of hospitalization (17,18). Whether RSV loads vary by subgroup and whether RSV subgroup-specific variations in disease severity are the result of differences in RSV load have not been studied.…”
mentioning
confidence: 99%
“…Sommige onderzoekers suggereren een positieve relatie hiertussen [63][64][65][66][67][68][69][70][71][72] , terwijl anderen die relatie niet zien [73][74][75][76][77][78] In de kindergeneeskunde praktijk is virale diagnostiek vaak gebruikt als een enkelvoudige meting bij eerste presentatie van een kind op de spoedeisende hulpafdeling of polikliniek. Deze omstandigheden zijn echter niet optimaal om de relatie tussen viral load en ziekte-ernst te bestuderen, omdat viral load een dynamisch proces is.…”
Section: Viral Loadunclassified
“…Current research focuses on new vaccination strategies and a better understanding of the immune response against Bordetella pertussis. Recently, the World Health Organization (WHO) recommended vaccination during pregnancy as an additional strategy to routine infant vaccinations in order to prevent pertussis in newborns 78 . In the Netherlands,…”
Section: General Introduction 15mentioning
confidence: 99%